Case Study on FX Forward Transaction Decisions To Customers Of PT Bank XXXX Treasury Regional Area Semarang - Ade Putra Achdijalsjah; I Made Sukresna (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Given the positive trend of export and import developments in Central Java in 2016-2020, it has an impact on increasing the volume of customer forex transactions, but customers who are active in FX. forward is only under 10%. Based on this phenomenon, it is interesting to conduct research with the aim of knowing the factors that are taken into account by customers in making decisions to choose and refuse to make FX transactions. forward. The research was conducted with a qualitative design with a case study approach. Primary data was taken using an open interview technique to 3 (three) informants, with the criteria of customers who already have an agreement at the same time who have and have not decided on FX forward transactions, and customers who do not have an agreement and have not decided on FX forward transactions. The analysis technique uses qualitative analysis which is presented in a narrative manner. The results of the study reveal the concepts of: (1). Factors that are taken into consideration by customers in making decisions to choose to conduct FX transactions. forward consists of: buffer stock, new investment opportunities, low profitability, high current liabilities, global events, state government policies related to foreign exchange rates, and low competitors. (2). Factors taken into consideration by customers in making decisions not to choose to conduct FX transactions. forward consists of: USD/IDR movements that are not in line with customer expectations, increased profitability, high cash turnover.